2008
DOI: 10.1016/j.jaut.2007.10.005
|View full text |Cite
|
Sign up to set email alerts
|

RDP58 inhibits T cell-mediated bladder inflammation in an autoimmune cystitis model

Abstract: Interstitial cystitis (IC) is a chronic inflammatory condition of the urinary bladder with a strong autoimmune component. Currently, the major challenge in IC treatment is the development of effective therapies. RDP58 is a novel D-amino acid decapeptide with potent immunosuppressive activity. In this study, we investigated whether RDP58 was effective as an intravesical agent for treating bladder autoimmune inflammation in a transgenic mouse model (URO-OVA mice). URO-OVA mice were adoptively transferred with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
(64 reference statements)
1
35
0
Order By: Relevance
“…URO-OVA mice developed bladder inflammation at day 7 after cystitis induction as described previously [25,33,34]. The inflamed bladders exhibited prominent cellular infiltration, edema, and hyperemia (Fig 1A, top panel; Table 1, score: 3+) as well as increased mast cell counts (Fig 1B; S3 Fig).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…URO-OVA mice developed bladder inflammation at day 7 after cystitis induction as described previously [25,33,34]. The inflamed bladders exhibited prominent cellular infiltration, edema, and hyperemia (Fig 1A, top panel; Table 1, score: 3+) as well as increased mast cell counts (Fig 1B; S3 Fig).…”
Section: Resultsmentioning
confidence: 60%
“…We previously demonstrated that the URO-OVA model was responsive to intravesical treatment with anti-inflammatory agents such as dimethyl sulfoxide [33] and RDP58 [34]. We observed that both agents inhibited bladder inflammation through suppressing T cell activity and/or viability in the animal model.…”
Section: Discussionmentioning
confidence: 99%
“…URO-OVA/OT-I mice, derived by crossing URO-OVA mice with transgenic mice that express an OVA-specific CD8+ T cell receptor (OT-I mice), spontaneously develop autoimmune cystitis [43]. However, OVA is not an endogenous antigen of bladder, and the bladder urodynamic changes and pain correlates of the IC/PBS phenotype have not been characterized in those transgenic models [43], [44]. A spontaneous model of IC/PBS was described in cats [48], however this has not been studied extensively in the scientific community due its unknown etiology and the high costs of maintaining and handling cats, which require involvement of a veterinarian [15].…”
Section: Discussionmentioning
confidence: 99%
“…MLN-0415, an IKKβ inhibitor developed by Millennium to target the NF-κB pathway, was discontinued at phase I, because of its adverse effects. RDP-58, a decapeptide that targets IRAK complex formation, is in phase II clinical trials for Crohn’s disease and ulcerative colitis [139, 140]. …”
Section: Therapeutic Approaches Targeting Tlrsmentioning
confidence: 99%